MEKTEPLERDE YADRO FIZIKASÍ BÓLIMIN OQÍTÍWDÍ JETILISTIRIW JOLLARÍ (Mektep fizika muǵállimlerine metodikalıq járdem) - Kalilaev, F.K. (SCIENCE and SOCIETY, 2023)
There article deals with the teaching of physics in schools with the introduction of additional concepts related to the topics of nuclear physics.
Keywords: nuclear reaction; proton; neutron; isotope; binding energy; nuclear forces; thermonuclear fusion